Spherical alumina supported catalyst with double pore distribution and preparation method and application thereof

By using a spherical alumina-supported catalyst with double-pore distribution, carbon disulfide is efficiently removed under normal temperature and pressure, the problems of complex process and high energy consumption in the existing dry desulfurization technology are solved, and efficient and fine desulfurization effect is achieved.

CN119733565APending Publication Date: 2025-04-01CHINA RES INST OF DAILY CHEM IND
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411876716.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

In the existing dry desulfurization technology, the two-step reaction process of carbon disulfide is complex and has high energy consumption, which poses safety hazards and complex operation problems.

Method used

A spherical alumina supported catalyst with a double-porous distribution spherical alumina support, which simplifies the desulfurization process by performing a desulfurization reaction under normal temperature and pressure, using a spherical alumina support with a sulfonated metal phthalocyanine or metal phthalocyanine sulfonate as active components.

Benefits of technology

It achieves efficient and fine removal of carbon disulfide at room temperature and pressure, reduces energy consumption and operational complexity, and has a desulfurization efficiency of more than 98%.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a spherical alumina supported catalyst with a double pore distribution, a preparation method and an application thereof, and belongs to the field of air pollution control technology. The catalyst is composed of a spherical alumina carrier with a double pore distribution and an active component, and the active component is a sulfonated metal phthalocyanine or a metal phthalocyanine sulfonate. The mass fraction of the sulfonated metal phthalocyanine or the metal phthalocyanine sulfonate in the catalyst is 0.5% to 30%. The spherical alumina supported catalyst with a double pore distribution prepared by the invention can be applied to the fine removal of carbon disulfide in the tail gas of viscose chemical fiber production; the removal process can be carried out at normal temperature and pressure, the reaction conditions are mild, the operation process is simple, and the operating cost is low; the prepared catalyst exhibits excellent desulfurization efficiency, and the desulfurization efficiency is as high as more than 98%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a spherical alumina supported catalyst with double pore distribution and a preparation method and application thereof, belonging to the technical field of air pollution control. Background Art

[0002] Carbon disulfide (CS2) exists in large quantities in the exhaust gas emitted by the chemical, printing and dyeing, rubber and other industries. Carbon disulfide has the characteristics of high toxicity, high volatility and low boiling point. Carbon disulfide can cause great harm to human health and is listed as a Class 2B carcinogen by the International Agency for Research on Cancer (IARC). Carbon disulfide can enter the human body through breathing and skin, causing harm to various organs of the human body. Inhaling high concentrations of carbon disulfide in a short period of time can cause acute poisoning, and symptoms such as headache, dizziness, and vomiting may occur. Long-term exposure to low concentrations of carbon disulfide can damage the nervous system and even cause symptoms such as embryo teratogenesis and congenital defects in offspring. In addition, carbon disulfide can also cause great harm to the environment; for example: carbon disulfide can generate sulfur dioxide through photolysis-oxidation, which eventually causes acid rain hazards; carbon disulfide can also indirectly or directly generate carbon dioxide through combustion, photolysis, hydrolysis or with hydrogen sulfide at high temperatures, exacerbating global climate change.

[0003] At present, the commonly used desulfurization technologies are divided into wet desulfurization and dry desulfurization. Wet desulfurization is usually used in places with high sulfur concentration and large flue gas processing volume. Its disadvantage is that during the wet desulfurization process, the flue gas will be humidified and cooled, which may cause the flue gas to be difficult to diffuse and emit white smoke. Dry desulfurization is often used for the fine removal of sulfides. The commonly used dry desulfurization technology is a two-step method. First, carbon disulfide needs to be hydrogenated or hydrolyzed under high temperature conditions to convert it into hydrogen sulfide, and then the hydrogen sulfide is removed with a desulfurizer. The two-step reaction can be completed. This process is complicated to operate and has high energy consumption. Chinese patent CN105080487A discloses a modified activated carbon desulfurization adsorbent and a preparation method thereof. The catalyst is composed of an activated carbon carrier and a modified material phthalocyanine cobalt sulfonate and copper. However, the desulfurization process in this patent needs to control certain temperature and pressure conditions, and there are certain energy consumption and safety hazards.

[0004] Therefore, a new technical solution is urgently needed to achieve fine removal of carbon disulfide. Summary of the invention

[0005] In order to solve the problems of two-step reaction of carbon disulfide in dry desulfurization, complex process and high energy consumption, the present invention provides a spherical alumina-supported catalyst with a double-pore distribution, a preparation method thereof and an application in removing carbon disulfide. The catalyst can efficiently and finely remove residual carbon disulfide in the tail gas of viscose chemical fiber production at normal temperature and pressure.

[0006] The catalyst carrier used in the present invention is a spherical alumina with a double pore distribution, which has the advantages of double pore distribution, good mechanical properties, and high specific surface area: the micropores and mesopores are conducive to increasing the specific surface area of ​​alumina, thereby loading more active components and generating more active sites; the macropores are conducive to reducing the diffusion resistance in the carrier pores, allowing carbon disulfide molecules to migrate rapidly in the pores, effectively improving the catalytic activity and catalytic efficiency of the catalyst. The active component used in the present invention is a sulfonated metal phthalocyanine or a metal phthalocyanine sulfonate, and its molecules have extremely strong chemical reaction activity, which is due to its special electronic structure: the center of the molecule is surrounded by a large ring composed of 4 nitrogen atoms, and the metal atom at the center is surrounded by five ligands. The catalyst structure provided by the present invention enables the active component to have a strong affinity for electrons, especially to easily capture sulfur ions in sulfides. The catalyst prepared by the present invention shows strong binding force and catalytic activity to carbon disulfide, and the catalyst prepared by the present invention achieves a good desulfurization effect.

[0007] The invention provides a spherical alumina supported catalyst with a double pore distribution, which is composed of a spherical alumina carrier with a double pore distribution and an active component, wherein the active component is a sulfonated metal phthalocyanine or a metal phthalocyanine sulfonate, and the mass fraction of the sulfonated metal phthalocyanine or the metal phthalocyanine sulfonate in the catalyst is 0.5% to 30%.

[0008] The present invention provides a method for preparing the above-mentioned spherical alumina supported catalyst with double pore distribution, comprising the following steps: (1) Stirring and dispersing the weighed sulfonated metal phthalocyanine or metal phthalocyanine sulfonate and an organic solvent at a certain temperature to obtain a uniform precursor solution; (2) The spherical alumina carrier with a bi-porous distribution is transferred to the above-mentioned precursor solution, and high-speed stirring is continued to ensure thorough mixing. After low-temperature evaporation, the solution is transferred to a muffle furnace for calcination to finally obtain a spherical alumina supported catalyst with a bi-porous distribution.

[0009] The pore size distribution ratio of aluminum oxide in the catalyst is as follows: the part with pore size >100nm accounts for 40-60% of the total pore volume; the part with pore size <30nm accounts for about 10-30% of the total pore volume, and the remaining pore size is between 30-100 nm.

[0010] The sulfonated metal phthalocyanine in the catalyst is one of sulfonated phthalocyanine iron, sulfonated phthalocyanine cobalt and sulfonated phthalocyanine nickel; the metal phthalocyanine sulfonate is one of sodium phthalocyanine iron sulfonate, sodium phthalocyanine cobalt sulfonate, sodium phthalocyanine nickel sulfonate, potassium phthalocyanine iron sulfonate, potassium phthalocyanine cobalt sulfonate and potassium phthalocyanine nickel sulfonate.

[0011] In step (1), the suitable organic solvent is one of isopropanol, anhydrous ethanol, cyclohexane and acetone.

[0012] In step (1), the mass ratio of the sulfonated metal phthalocyanine or metal phthalocyanine sulfonate to the organic solvent is 1:100 to 1:1000.

[0013] In step (1), the stirring and dispersing temperature of the sulfonated metal phthalocyanine or metal phthalocyanine sulfonate in the organic solvent is 20 to 50° C. and the time is 30 to 240 minutes.

[0014] In step (2), the low temperature evaporation conditions are: drying at 40-70°C for 3-8 h.

[0015] In step (2), the calcination conditions are: calcination at 200-600°C for 1-6 h.

[0016] The present invention provides the use of the above-mentioned spherical alumina supported catalyst with double pore distribution in fine removal of carbon disulfide in tail gas of viscose chemical fiber production, and the specific method is as follows: (1) Check the airtightness of the Bao's gas sampling tube and confirm that the sampling tube is airtight; (2) Take 1-2 g of spherical alumina-supported catalyst with double-pore distribution and put it at the bottom of the absorption container. At room temperature and pressure, continuously introduce CS2 gas (CS2 / N2 mixed gas) with a concentration of 50 ppm from the inner tube inlet of the Bao gas sampling tube. After the gas is absorbed by the prepared catalyst at the bottom of the absorption container, the remaining gas escapes from the sampling tube through the outer tube outlet. The outlet is connected to a CS2 standard detection tube to detect the CS2 concentration in the escaping gas.

[0017] Beneficial effects of the present invention: (1) The catalyst carrier used in the present invention is a spherical alumina with a double pore distribution, which has the advantages of double pore distribution and good mechanical properties; the active component used in the present invention exhibits strong adsorption activity for carbon disulfide, which can effectively improve the catalytic efficiency of the catalyst; (2) The process for removing residual carbon disulfide from tail gas produced by viscose chemical fiber production according to the present invention can be carried out at room temperature and pressure, with mild reaction conditions, simple operation process and low operating cost; (3) In the process of removing residual carbon disulfide in the tail gas of viscose chemical fiber production described in the present invention, the prepared catalyst exhibits excellent desulfurization efficiency, and the desulfurization efficiency is as high as more than 98%. DETAILED DESCRIPTION

[0018] The present invention is further illustrated by the following examples, but is not limited to the following examples.

[0019] Comparative Example: Check the airtightness of the Bao's gas sampling tube and confirm that the sampling tube is airtight. Take 1 g of spherical alumina with double pore distribution and put it at the bottom of the absorption container. At room temperature and pressure, continuously pass CS2 gas (CS2 / N2 mixed gas) with a concentration of 50 ppm from the inner tube inlet of the Bao's gas sampling tube at a flow rate of 15 mL / min. After the gas is absorbed by alumina at the bottom of the absorption container, the remaining gas escapes from the sampling tube through the outer tube outlet. After 3 hours, connect the CS2 detection tube at the outlet to detect the CS2 concentration in the escaping gas. After the gas with a CS2 concentration of 50 ppm is adsorbed by alumina, the CS2 concentration is 45 ppm.

[0020] The following is a specific embodiment of the present invention, in which the spherical alumina carrier with a double pore distribution is used, the pore size of 100 nm or more accounts for about 60% of the total pore volume, and the pore size of 30 nm or less accounts for about 20% of the total pore volume. The spherical alumina can be directly purchased. Example 1

[0021] Place a four-necked flask in a water bath, place a thermometer and an electric stirring paddle in the four-necked flask in turn, raise the temperature to 40°C, weigh 0.03 g of sulfonated phthalocyanine iron and 50 mL of acetone solution in the four-necked flask in turn, and start the stirring paddle for high-speed stirring. After stirring for 120 min, add 1 g of a spherical alumina carrier with a bi-porous distribution, and the weight percentage of sulfonated phthalocyanine iron is 3%. After continuing to stir at high speed for 30 min, transfer it to an open glass dish, place it in a 50°C oven to dry for 3 h, and finally calcine it at 450°C in a muffle furnace for 3 h to obtain a sulfonated phthalocyanine iron catalyst supported by a spherical alumina with a bi-porous distribution.

[0022] Check the airtightness of the Bao's gas sampling tube and confirm that the sampling tube is airtight. Take 1 g of the prepared catalyst product and put it at the bottom of the absorption container. At room temperature and pressure, continuously introduce CS2 gas (CS2 / N2 mixed gas) with a concentration of 50 ppm from the inner tube inlet of the Bao's gas sampling tube at a flow rate of 15 mL / min. After the gas is absorbed by the prepared catalyst at the bottom of the absorption container, the remaining gas escapes from the sampling tube through the outer tube outlet. After 3 hours, connect the CS2 standard detection tube at the outlet to detect the CS2 concentration in the escaping gas. After the gas with a CS2 concentration of 50 ppm is adsorbed by the prepared catalyst, the CS2 concentration drops to 0.65 ppm, and the desulfurization rate is 98.7%. Compared with the comparative example, the catalyst shows a good adsorption effect on CS2. Example 2

[0023] Place a four-necked flask in a water bath, place a thermometer and an electric stirring paddle in the four-necked flask in turn, raise the temperature to 40°C, weigh 0.05 g of sulfonated cobalt phthalocyanine and 60 mL of anhydrous ethanol solution in the four-necked flask in turn, and start the stirring paddle for high-speed stirring. After stirring for 120 min, add 1 g of a spherical alumina carrier with a bi-porous distribution, and the weight percentage of sulfonated cobalt phthalocyanine is 5%. After continuing to stir at high speed for 30 min, transfer it to an open glass dish, place it in a 50°C oven to dry for 3 h, and finally calcine it at 450°C in a muffle furnace for 2 h to obtain a sulfonated cobalt phthalocyanine salt catalyst supported by a spherical alumina with a bi-porous distribution.

[0024] Check the airtightness of the Bao's gas sampling tube and confirm that the sampling tube is airtight. Take 1 g of the prepared catalyst product and put it at the bottom of the absorption container. At room temperature and pressure, continuously introduce CS2 gas (CS2 / N2 mixed gas) with a concentration of 50 ppm from the inner tube inlet of the Bao's gas sampling tube at a flow rate of 15 mL / min. After the gas is absorbed by the prepared catalyst at the bottom of the absorption container, the remaining gas escapes from the sampling tube through the outer tube outlet. After 3 hours, connect the CS2 standard detection tube at the outlet to detect the CS2 concentration in the escaping gas. After the gas with a CS2 concentration of 50 ppm is adsorbed by the prepared catalyst, the CS2 concentration drops to 0.5 ppm, and the desulfurization rate is 99%. Compared with the comparative example, the catalyst shows a good adsorption effect on CS2. Example 3

[0025] Place a four-necked flask in a water bath, place a thermometer and an electric stirring paddle in the four-necked flask in turn, raise the temperature to 40°C, weigh 0.05 g of sulfonated nickel phthalocyanine and 60 mL of cyclohexane solution in the four-necked flask in turn, and start the stirring paddle for high-speed stirring. After stirring for 180 min, add 1 g of a spherical alumina carrier with a bi-porous distribution, and the weight percentage of sulfonated nickel phthalocyanine is 5%. After continuing to stir at high speed for 30 min, transfer it to an open glass dish, place it in a 60°C oven to dry for 1 h, and finally calcine it at 500°C in a muffle furnace for 2 h to obtain a sulfonated nickel phthalocyanine catalyst supported by a spherical alumina with a bi-porous distribution.

[0026] Check the airtightness of the Bao's gas sampling tube and confirm that the sampling tube is airtight. Take 1 g of the prepared catalyst product and put it at the bottom of the absorption container. At room temperature and pressure, continuously introduce CS2 gas (CS2 / N2 mixed gas) with a concentration of 50 ppm from the inner tube inlet of the Bao's gas sampling tube at a flow rate of 15 mL / min. After the gas is absorbed by the prepared catalyst at the bottom of the absorption container, the remaining gas escapes from the sampling tube through the outer tube outlet. After 3 hours, connect the CS2 standard detection tube at the outlet to detect the CS2 concentration in the escaping gas. After the gas with a CS2 concentration of 50 ppm is adsorbed by the prepared catalyst, the CS2 concentration drops to 0.55 ppm, and the desulfurization rate is 98.9%. Compared with the comparative example, the catalyst shows a good adsorption effect on CS2. Example 4

[0027] Place a four-necked flask in a water bath, place a thermometer and an electric stirring paddle in the four-necked flask in turn, raise the temperature to 40°C, weigh 0.1 g of sodium phthalocyanine iron sulfonate and 20 mL of isopropanol solution in the four-necked flask in turn, and start the stirring paddle for high-speed stirring. After stirring for 30 min, add 1 g of a spherical alumina carrier with a bi-porous distribution, and the weight percentage of sodium phthalocyanine iron sulfonate is 10%. After continuing to stir at high speed for 30 min, transfer it to an open glass dish, place it in a 50°C oven to dry for 4 h, and finally calcine it at 200°C in a muffle furnace for 5 h to obtain a sodium phthalocyanine iron sulfonate catalyst supported by a spherical alumina with a bi-porous distribution.

[0028] Check the airtightness of the Bao's gas sampling tube and confirm that the sampling tube is airtight. Take 1 g of the prepared catalyst product and put it at the bottom of the absorption container. At room temperature and pressure, continuously introduce CS2 gas (CS2 / N2 mixed gas) with a concentration of 50 ppm from the inner tube inlet of the Bao's gas sampling tube at a flow rate of 15 mL / min. After the gas is absorbed by the prepared catalyst at the bottom of the absorption container, the remaining gas escapes from the sampling tube through the outer tube outlet. After 3 hours, connect the CS2 standard detection tube at the outlet to detect the CS2 concentration in the escaping gas. After the gas with a CS2 concentration of 50 ppm is adsorbed by the prepared catalyst, the CS2 concentration drops to 0.4 ppm, and the desulfurization rate is 99.2%. Compared with the comparative example, the catalyst shows a good adsorption effect on CS2. Example 5

[0029] Place a four-necked flask in a water bath, place a thermometer and an electric stirring paddle in the four-necked flask in turn, raise the temperature to 40°C, weigh 0.1 g of sodium phthalocyanine nickel sulfonate and 30 mL of acetone solution in the four-necked flask in turn, and start the stirring paddle for high-speed stirring. After stirring for 60 min, add 1 g of a spherical alumina carrier with a bi-porous distribution, and the weight percentage of sodium phthalocyanine nickel sulfonate is 10%. After continuing to stir at high speed for 30 min, transfer it to an open glass dish, place it in a 60°C oven to dry for 3 h, and finally calcine it at 300°C in a muffle furnace for 4 h to obtain a sodium phthalocyanine nickel sulfonate catalyst supported by a spherical alumina with a bi-porous distribution.

[0030] Check the airtightness of the Bao's gas sampling tube and confirm that the sampling tube is airtight. Take 1 g of the prepared catalyst product and put it at the bottom of the absorption container. At room temperature and pressure, continuously introduce CS2 gas (CS2 / N2 mixed gas) with a concentration of 50 ppm from the inner tube inlet of the Bao's gas sampling tube at a flow rate of 15 mL / min. After the gas is absorbed by the prepared catalyst at the bottom of the absorption container, the remaining gas escapes from the sampling tube through the outer tube outlet. After 3 hours, connect the CS2 standard detection tube at the outlet to detect the CS2 concentration in the escaping gas. After the gas with a CS2 concentration of 50 ppm is adsorbed by the prepared catalyst, the CS2 concentration drops to 0.25 ppm, and the desulfurization rate is 99.5%. Compared with the comparative example, the catalyst shows excellent adsorption effect on CS2. Example 6

[0031] Place a four-necked flask in a water bath, place a thermometer and an electric stirring paddle in the four-necked flask in turn, raise the temperature to 40°C, weigh 0.2 g of sodium phthalocyanine cobalt sulfonate and 40 mL of acetone solution in the four-necked flask in turn, and start the stirring paddle for high-speed stirring. After stirring for 90 min, add 1 g of a spherical alumina carrier with a bi-porous distribution, and the weight percentage of sodium phthalocyanine cobalt sulfonate is 20%. After continuing to stir at high speed for 30 min, transfer it to an open glass dish, place it in a 60°C oven to dry for 3 h, and finally calcine it at 450°C in a muffle furnace for 3 h to obtain a sodium phthalocyanine cobalt sulfonate catalyst supported by a spherical alumina with a bi-porous distribution.

[0032] Check the airtightness of the Bao's gas sampling tube and confirm that the sampling tube is airtight. Take 1 g of the prepared catalyst product and put it at the bottom of the absorption container. At room temperature and pressure, continuously introduce CS2 gas (CS2 / N2 mixed gas) with a concentration of 50 ppm from the inner tube inlet of the Bao's gas sampling tube at a flow rate of 15 mL / min. After the gas is absorbed by the prepared catalyst at the bottom of the absorption container, the remaining gas escapes from the sampling tube through the outer tube outlet. After 3 hours, connect the CS2 standard detection tube at the outlet to detect the CS2 concentration in the escaping gas. After the gas with a CS2 concentration of 50 ppm is adsorbed by the prepared catalyst, the CS2 concentration drops to 0.5 ppm, and the desulfurization rate is 99%. Compared with the comparative example, the catalyst shows a good adsorption effect on CS2. Example 7

[0033] Place a four-necked flask in a water bath, place a thermometer and an electric stirring paddle in the four-necked flask in turn, raise the temperature to 40°C, weigh 0.3 g of potassium phthalocyanine iron sulfonate and 60 mL of cyclohexane solution in the four-necked flask in turn, and start the stirring paddle for high-speed stirring. After stirring for 240 min, add 1 g of a spherical alumina carrier with a bi-porous distribution, and the weight percentage of potassium phthalocyanine iron sulfonate is 30%. After continuing to stir at high speed for 30 min, transfer it to an open glass dish, place it in a 60°C oven to dry for 6 h, and finally calcine it at 550°C in a muffle furnace for 2 h to obtain a bi-porous spherical alumina-supported potassium phthalocyanine iron sulfonate catalyst.

[0034] Check the airtightness of the Bao's gas sampling tube and confirm that the sampling tube is airtight. Take 1 g of the prepared catalyst product and put it at the bottom of the absorption container. At room temperature and pressure, continuously introduce CS2 gas (CS2 / N2 mixed gas) with a concentration of 50 ppm from the inner tube inlet of the Bao's gas sampling tube at a flow rate of 15 mL / min. After the gas is absorbed by the prepared catalyst at the bottom of the absorption container, the remaining gas escapes from the sampling tube through the outer tube outlet. After 3 hours, connect the CS2 standard detection tube at the outlet to detect the CS2 concentration in the escaping gas. After the gas with a CS2 concentration of 50 ppm is adsorbed by the prepared catalyst, the CS2 concentration drops to 0.6 ppm, and the desulfurization rate is 98.8%. Compared with the comparative example, the catalyst shows a good adsorption effect on CS2. Example 8

[0035] Place a four-necked flask in a water bath, place a thermometer and an electric stirring paddle in the four-necked flask in turn, raise the temperature to 40°C, weigh 0.25 g of potassium phthalocyanine cobalt sulfonate and 60 mL of cyclohexane solution in the four-necked flask in turn, and start the stirring paddle for high-speed stirring. After stirring for 240 min, add 1 g of a spherical alumina carrier with a bi-porous distribution, and the weight percentage of potassium phthalocyanine cobalt sulfonate is 25%. After continuing to stir at high speed for 30 min, transfer it to an open glass dish, place it in a 50°C oven to dry for 6 h, and finally calcine it at 550°C in a muffle furnace for 1 h to obtain a spherical alumina-supported potassium phthalocyanine cobalt sulfonate catalyst with a bi-porous distribution.

[0036] Check the tightness of the Bao's gas sampling tube and confirm that the sampling tube is airtight. Take 1 g of the prepared catalyst product and put it at the bottom of the absorption container. At room temperature and pressure, continuously pass CS2 gas (CS2 / N2 mixed gas) with a concentration of 50 ppm from the inner tube inlet of the Bao's gas sampling tube at a flow rate of 15 mL / min. After the gas is absorbed by the prepared catalyst at the bottom of the absorption container, the remaining gas escapes from the sampling tube through the outer tube outlet. After 5 hours, connect the CS2 standard detection tube at the outlet to detect the CS2 concentration in the escaping gas. After the gas with a CS2 concentration of 50 ppm is adsorbed by the prepared catalyst, the CS2 concentration drops to 0.55 ppm, and the desulfurization rate is 98.9%. Compared with the comparative example, the catalyst shows a good adsorption effect on CS2. Example 9

[0037] Place a four-necked flask in a water bath, place a thermometer and an electric stirring paddle in the four-necked flask in turn, raise the temperature to 40°C, weigh 0.3 g of potassium phthalocyanine nickel sulfonate and 60 mL of cyclohexane solution in the four-necked flask in turn, and start the stirring paddle for high-speed stirring. After stirring for 240 min, add 2 g of a spherical alumina carrier with a bi-porous distribution, and the weight percentage of potassium phthalocyanine iron sulfonate is 15%. After continuing to stir at high speed for 30 min, transfer it to an open glass dish, place it in a 60°C oven to dry for 6 h, and finally calcine it at 600°C in a muffle furnace for 1 h to obtain a bi-porous spherical alumina-supported potassium phthalocyanine iron sulfonate catalyst.

[0038] Check the airtightness of the Bao's gas sampling tube and confirm that the sampling tube is airtight. Take 2 g of the prepared catalyst product and put it at the bottom of the absorption container. At room temperature and pressure, continuously introduce CS2 gas (CS2 / N2 mixed gas) with a concentration of 50 ppm from the inner tube inlet of the Bao's gas sampling tube at a flow rate of 15 mL / min. After the gas is absorbed by the prepared catalyst at the bottom of the absorption container, the remaining gas escapes from the sampling tube through the outer tube outlet. After 3 hours, connect the CS2 standard detection tube at the outlet to detect the CS2 concentration in the escaping gas. After the gas with a CS2 concentration of 50 ppm is adsorbed by the prepared catalyst, the CS2 concentration drops to 0.4 ppm, and the desulfurization rate is 99.2%. Compared with the comparative example, the catalyst shows a good adsorption effect on CS2.

Claims

1. A spherical alumina supported catalyst with a double pore distribution, characterized in that: The catalyst consists of a spherical aluminum oxide carrier with double pore distribution and an active component, wherein the active component is sulfonated metal phthalocyanine or metal phthalocyanine sulfonate, and the mass fraction of the sulfonated metal phthalocyanine or metal phthalocyanine sulfonate in the catalyst is 0.5% to 30%.

2. The spherical alumina supported catalyst with dual pore distribution according to claim 1, characterized in that: The pore size distribution ratio of aluminum oxide in the catalyst is as follows: the part with pore size >100nm accounts for 40-60% of the total pore volume; the part with pore size <30nm accounts for 10-30% of the total pore volume, and the remaining pore size is between 30-100 nm.

3. The spherical alumina supported catalyst with dual pore distribution according to claim 1, characterized in that: The sulfonated metal phthalocyanine in the catalyst is one of sulfonated phthalocyanine iron, sulfonated phthalocyanine cobalt and sulfonated phthalocyanine nickel; the metal phthalocyanine sulfonate is one of sodium phthalocyanine iron sulfonate, sodium phthalocyanine cobalt sulfonate, sodium phthalocyanine nickel sulfonate, potassium phthalocyanine iron sulfonate, potassium phthalocyanine cobalt sulfonate and potassium phthalocyanine nickel sulfonate.

4. A method for preparing a spherical alumina supported catalyst with a double pore distribution according to any one of claims 1 to 3, characterized in that The following steps are involved: (1) Mixing the weighed sulfonated metal phthalocyanine or metal phthalocyanine sulfonate with an organic solvent, stirring and dispersing, and obtaining a uniform precursor solution; (2) The spherical alumina carrier with a bi-porous distribution is transferred to the above-mentioned precursor solution, and high-speed stirring is continued to ensure thorough mixing. After low-temperature evaporation, the solution is transferred to a muffle furnace for calcination to finally obtain a spherical alumina supported catalyst with a bi-porous distribution.

5. The method for preparing a spherical alumina supported catalyst with a dual pore distribution according to claim 4, characterized in that: In step (1), the organic solvent is one of isopropanol, anhydrous ethanol, cyclohexane and acetone; and the mass ratio of the sulfonated metal phthalocyanine or metal phthalocyanine sulfonate to the organic solvent is 1:100 to 1:1000.

6. The method for preparing a spherical alumina supported catalyst with a dual pore distribution according to claim 4, characterized in that: In step (1), the stirring and dispersing temperature of the sulfonated metal phthalocyanine or metal phthalocyanine sulfonate in the organic solvent is 20 to 50° C. and the time is 30 to 240 minutes.

7. The method for preparing a spherical alumina supported catalyst with a dual pore distribution according to claim 4, characterized in that: In step (2), the low temperature evaporation conditions are: drying at 40-70°C for 3-8 h.

8. The method for preparing a spherical alumina supported catalyst with a dual pore distribution according to claim 4, characterized in that: In step (2), the calcination conditions are: calcination at 200-600°C for 1-6 h.

9. Use of the spherical alumina supported catalyst with a double pore distribution as claimed in any one of claims 1 to 3 in the fine removal of carbon disulfide from tail gas in viscose chemical fiber production.

10. The use according to claim 9, characterized in that The specific method is as follows: (1) Check the airtightness of the Bao's gas sampling tube and confirm that the sampling tube is airtight; (2) Take 1-2 g of spherical alumina-supported catalyst with double-pore distribution and put it at the bottom of the absorption container. At room temperature and pressure, continuously introduce CS2 gas with a concentration of 50 ppm from the inner tube inlet of the Bao gas sampling tube. After the gas is absorbed by the prepared catalyst at the bottom of the absorption container, the remaining gas escapes from the sampling tube through the outer tube outlet. The outlet is connected to a CS2 standard detection tube to detect the CS2 concentration in the escaping gas.

Citation Information

Patent Citations

  • Active carbon desulphurization adsorbent loaded with cobalt phthalocyanine sulfonate and copper and preparation method thereof

    CN105080487A